Case report: A case of Acute Macular Neuroretinopathy secondary to Influenza A virus during Long COVID - Zhang, Jiaqi; Xia, Yihao; Li, Xiaodong; He, Runxi; Xie, Xuejun (Frontiers in Immunology, 2024)
Ocular abnormalities have been reported in association with viral infections, including Long COVID, a debilitating illness caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This report presents a case of a female patient diagnosed with Acute Macular Neuroretinopathy (AMN) following an Influenza A virus infection during Long COVID who experienced severe inflammation symptoms and ocular complications. We hypothesize that the rare occurrence of AMN in this patient could be associated with the immune storm secondary to the viral infection during Long COVID.